Unravelling the phenolic compound reserves, antioxidant and enzyme inhibitory activities of an endemic plant species, Achillea pseudoaleppica - Yilmaz, Mustafa Abdullah; Taslimi, Parham; Kilic, Omer; Gulcin, Ilhami; Dey, Abhijit; Bursal, Ercan (Taylor & Francis Inc, 2021)
The present ethnobotanical study unravelled the phenolic reservoir (UHPLC-MS/TQ-MS) and pharmacological activity (antioxidant and enzyme inhibitory activities) of an endemic plant, Achillea pseudoaleppica Hub.-Mor. (Asteraceae). The effective antioxidant properties of ethanol and water extracts of A. pseudoaleppica leaves were determined by using six different in vitro bioanalytical methods including three reducing antioxidant methods and three radical scavenging antioxidant methods. In the other step of the study, the enzyme inhibitory effects of water and ethanol extracts of A. pseudoaleppica were determined against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), alpha-amylase, and alpha-glucosidase enzymes. The ethanol extract was found to have effective inhibition potential for all four respected enzymes. The IC50 values of A. pseudoaleppica extract against AChE, BChE, alpha-amylase, and alpha-glucosidase enzymes were found to be 2.67 mg/mL, 4.55 mg/mL, 16.51 mg/mL, and 12.37 mg/mL, respectively. Also, UHPLC-MS/TQ-MS analyses revealed quinic acid as the most abundant phenolic compound of the water extract (31.12 +/- 1.65 mu g/mg) and ethanol extract (11.75 +/- 0.82 mu g/mg). In addition, the molecular docking interaction of the most abundant phenolic compound of A. pseudoaleppica (quinic acid) with AChE, BChE, alpha-amylase, and alpha-glucosidase target enzymes were evaluated using Chimera and AutoDock Vina softwares. In conclusion, the rich phenolic content and the potent antioxidant and enzyme inhibitory properties of A. pseudoaleppica extracts may support the widespread ethnobotanical use of the plant application. Communicated by Ramaswamy H. Sarma
Keywords: Achillea pseudoaleppica; antioxidant; enzyme inhibition; phenolic content; radical scavenging; In-Vitro Antioxidant; Essential Oil; Bioactive Compounds; Asteraceae; Anticholinesterase; Extracts